The Case for Embodied Instruction: The Instructor as a Source of Attentional and Social Cues in Video Lectures - Stull, Andrew T; Fiorella, Logan; Mayer, Richard E (Journal of educational psychology, 2021)
This study explores the role of the instructor's face and eye gaze as social and attentional cues in promoting learning from a video lecture on kidney physiology. In a 2 × 2 between-subjects design, 133 college students were randomly assigned to a gaze behavior condition and a video whiteboard type condition. The instructor either shifted her gaze between the learner and board (shifting) or only gazed at the board (fixed), and the instructor's gaze was either occluded (conventional whiteboard) or visible (transparent whiteboard) when facing the board. Learners' perceived engagement, gaze behavior, and learning were measured. Students in the conventional whiteboard group reported higher engagement and achieved higher posttest scores than students in the transparent whiteboard group (main effect of whiteboard), particularly when the instructor shifted her gaze between the learner and the board (whiteboard by gaze interaction). Furthermore, students in the conventional whiteboard condition attended more to the learning material on the board, whereas students in the transparent whiteboard group attended more to the instructor. Overall, learning was better when the instructor's social cues promoted engagement (i.e., by shifting gaze) without distracting learners from attending to the instructor's cues to attend to the whiteboard (i.e., by conventional whiteboards).